Evaluation and benefit of physico-chemical properties of physalis minima linn plant for food addictive: article - Ayub, Nor Shira; Che Radzi, Nurhaslina (2019)
The evaluation and benefits of physicochemical properties of Physalis Minima Linn plant were investigated. To identify these properties, the fruits for this plant need to obtain in powder form. Therefore, the fruit was washed, dried about 24 hours and grinded using a grinder machine with the size of sieve 0.25 mm to obtain physalis minima linn powder. The physicochemical parameter of this seed are bulk density, true density, porosity, water absorption index, water solubility index, oil absorption index, swelling index, percentage of solubility, foaming capacity, and foaming stability. It was observed that, the results value are 0.3358 g/mL, 2.1633 g/mL, 0.8466%, 93.673 g/g, 53.6 g/g, 2.9783 mL/g, 1.3424 g/g, 2.3539 g/g, 0.05%, 141.67%, respectively. The moisture content for root, leaf and branch for this plant also were analyzed and the result was obtaining are 90.44%, 88.12% and 94.74%, respectively. Due to high percentage in water absorption and water solubility properties, it helps consumer to relieve diarrhea and avoid constipation.